Partisipasi dan Keberhasilan Kelompok Wanita Tani dalam Pelaksanaan Budikdamber Program Pekarangan Pangan Lestari (P2L) di Kecamatan Lawang Kidul Kabupaten Muara Enim: Participation and Success of Women Farmers Group in The Implementation of The Budikdamber Pekarangan Pangan Lestari Program (P2L) in Lawang Kidul Subdistrict Muara Enim - oktarina, selly; rahmi bhakti izdmi (Sriwijaya Journal of Agribusiness and Biometrics in Agriculture Research, 2025)
The P2L program was a program initiated by the Food Security Agency (BKP) as an effort to expand the number of beneficiaries from homestead land. The objectives of this research are: 1) Measuring the level of participation of women farmers in implementing the Budikdamber P2L program, 2) Measuring the level of success of women farmers in implementing the Budikdamber P2L program, 3) Analyzing the relationship between the level of participation and success of women farmers in implementing the Budikdamber P2L program. This research was carried out in Tegal Rejo Village, Lawang Kidul District, Muara Enim Regency in December 2023. The research method used was a survey method. The data used were primary and secondary data. The results of this research were: 1) The level of participation of women farmers in implementing the Budikdamber program for Sustainable Food Farms (P2L) in Tegal Rejo Village as a whole is included in the high criteria where women farmers who are members of the Tegal Serasan women farmer group (KWT) participate actively in implementing Budikdamber starting from the collection stage decisions, implementation, benefits and evaluation. 2) The level of success of women farmers in implementing the Budikdamber Sustainable Food Farm (P2L) program in Tegal Rejo Village is included in the high criteria, where KWT Tegal Serasan is successful in implementing Budikdamber seen from production, marketing, price (economic aspects) and community welfare, empowerment society, environmental impact (social aspect). 3) The results of the Spearman test show that there is a significant relationship between the participation and success of women farmers in implementing the Budikdamber P2L program in Tegal Rejo Village, with a strong relationship (0.620).